Dapsone induced methemoglobinemia - Narula, Shubhank; Khosla, Pooja; Taneja, Vinus (International Journal of Research in Medical Sciences, 2024)
Increase in levels of methemoglobin is termed as methemoglobinemia which leads to organ level hypoxia. It can be congenital or acquired. In this case report we present a case of a middle-aged female with methemoglobinemia due to dapsone overdose and how immediate introduction of ascorbic acid, oxygen therapy and dapsone discontinuation cured the patient.